AB0395 Evaluation of the organ damage detected by systemic lupus international collaborating clinics/american college of rheumatology (slicc/acr) damage index. a monocentric cross-sectional study on 349 patients affected by systemic lupus erythematosus. (23rd January 2014) - Ceccarelli, F.; Massaro, L.; Perricone, C.; Leccese, I.; Truglia, S.; Miranda, F.; Pacucci, V. A.; Cipriano, E.; Martinelli, F.; Spinelli, F. R.; Alessandri, C.; Conti, F.; et al.
Abstract : Background: The survival and outcome of patients affected by Systemic Lupus Erythematosus (SLE) have improved dramatically over the past 50 years in terms of mortality and morbidity rates. However, the activity of disease and the long-term therapy could be associated with the development of a chronic damage Objectives: To evaluate organ damage using SLICC/ACR damage index (SDI) in a large monocentric and well-characterized cohort of patients affected by SLE and to investigate its correlation with clinical, demographic and laboratory features. Methods: Consecutive patients affected by SLE (revised ACR criteria) referring to a Lupus Clinic, were enrolled to perform a cross-sectional analysis. At each visit, the patients underwent complete physical examination, and the clinical and laboratory data were collected in a standardized computerized electronically-filled form. Chronic damage was evaluated in all the patients by using SDI. Results: In our study, 349 SLE patients (M/F 25/324; mean age at the onset ± SD 29.2±12 years, mean age ± SD 42.7±12.4 years, mean disease duration ± SD 164.9±105.2 months) were enrolled. A SDI value ≥ 1 was observed in 125 patients (35.8%), with a mean SDI value of 1.7±0.9 (range 1-5). Patients with SDI ≥ 1 showed significant higher mean values of age (38.8±11.3 vs 49.7±11.3) and disease duration (135.6±93.1 vs 217.5±105.4) compared with patients without chronic damage. Musculoskeletal was the system most frequently involved (41 patients, 33%), followed by neuropsychiatric manifestations and malignancies, both registered on 24 patients (19%) and the renal involvement (19 pts, 15%). Interestingly, neuropsychiatric manifestations were significantly associated with the presence of anticardiolipin antibodies (P=0.0005) and the occurrence of thrombotic events (P=0.0006). Moreover, regarding the development of malignancies, the most frequently types detected in the present cohort were thyroid and mammalian carcinoma (29.2% and 20.8% respectively), according with the higher incidence of disease in female subjects. Conclusions: A mild chronic damage, significantly associated with age and disease duration, involving primarily musculoskeletal system, was detected in the present monocentric, large cohort of SLE patients. Moreover, the role of anticardiolipin antibodies in the neuropsychiatric manifestations was underlined. These results confirm that the tight monitoring and the new available therapeutical options allow a better long-time control of disease, with consequent survival improvement. Disclosure of Interest: None Declared